Dan’e fukang decoction reduces hemorrhage in a rat model of mifepristone induced incomplete abortion and may correlate with cell adhesion molecule signaling interference - Ni, Qi-cheng; Zhong, Rui-hua; Yang, Ye; Li, Guo-ting; Yang, Wen-jie; Zhou, Jie-yun; Hu, Ying-yi; Wu, Jianhui; Zhu, Yan (Journal of ethnopharmacology, 2025)
Dan’e fukang decoction (DFD) is a traditional Chinese medicine formula. DFD obtains 10 herbs, including Salvia yunnanensis C.H.Wright (Zidanshen), Curcuma zedoaria (Christm.) Roscoe (Ezhu), Angelica sinensis (Oliv.) Diels (Danggui), Cyperus rotundus L. (Xiangfuzi), Corydalis yanhusuo (Y.H.Chou & Chun C. Hsu) W.T.Wang ex Z.Y.Su & C.Y.Wu, Bupleurum marginatum Wall. ex DC. (Yanhusuo), Sparganium stoloniferum (Buch.-Ham. ex Graebn.) Buch.-Ham. ex Juz. (Sanleng), Panax notoginseng (Burkill) F.H.Chen (Sanqi), Paeonia lactiflora Pall. (Shaoyao) and Glycyrrhiza uralensis Fisch. (Gancao). DFD is now clinically used for the treatment of menstrual irregularities, dysmenorrhea and menstrual discomfort caused by blood stasis and easing of endometriosis. Based on this, it is reasonable to presume that DFD may be effective in treating incomplete abortion and reducing postpartum bleeding, but no specific studies have been reported so far. To investigate the efficacy of Dan’e fukang decoction (DFD) in reducing prolonged vaginal bleeding followed by mifepristone induced incomplete abortion and explore the mechanisms of action of DFD in treating incomplete abortion. An incomplete abortion model of rat was established by single intragastrically administered 8.5 mg/kg mifepristone on the 7th day of pregnancy. From the 8th day of pregnancy, the abortive rats were administered solvent, a positive control drug, or different doses of DFD, respectively for seven consecutive days. The efficacy of DFD was assessed by measuring the vaginal bleeding volume of the rats. Four coagulation parameters and platelet counts were measured. Hematoxylin and eosin (HE) staining was performed to evaluate pathological changes in the uterine embryos. Serum levels of progesterone and estrogen were measured using ELISA. Network pharmacology and transcriptomics were used to predict potential targets and pathways for DFD to reduce hemorrhage. The levels of mRNA related to cell adhesion molecules (CAMs) were detected by RT-qPCR. The levels of progesterone and estrogen receptors and the proteins associated with CAMs pathway in uterine tissues were detected by Western Blot. DFD significantly reduced the volume of vaginal bleeding of the abortive rats and significantly downgraded the pathological scores of uterine embryos. DFD significantly increased serum levels of E2, and had no impact on serum levels of P4 and the protein expression of ER and PR in the uteri of the abortive rats. Pathways in cancer, lipid, focal adhesion and immune-related signaling were predicted to be influenced by DFD via the analysis of network pharmacology. The CAMs signaling was found the most critical pathway regulated by both mifepristone and DFD via RNA-seq assay, followed by axon guidance, basal cell carcinoma, hippo signaling pathway and neuroactive ligand-receptor interaction. Combining the two analytical methods, ICAM-1 was predicted likely the key targeted gene by DFD. Finally, DFD was validated to decrease the protein expression of ICAM-1, ITGB2, ITGB7 and RASSF5 in the uterine tissues, which correlated to suppress the CAMs signaling pathway. DFD significantly reduced hemorrhage. DFD significantly increased the serum levels of E2 and inhibited CAMs signaling pathway, which was likely to be involved in the mechanism of action of DFD facilitating residual uterine embryo expulsion in the rat model of incomplete abortion. [Display omitted] •DFD reduced hemorrhage in a rat model of induced incomplete abortion.•DFD facilitated the expulsion of residual embryos.•DFD upregulated serum levels of E2.•DFD suppressed cell adhesion molecules (CAMs) signaling pathway.